Remarks on Some Results of Extended Interpolative Hardy-Rogers-Geraghty-Wardowski Contractions and Ćirić-Reich-Rus Type F-Contractions - Dušan Bajović; Slobodanka Mitrović; Sandra Buhmiler; Stojan Radenovic (Sahand Communications in Mathematical Analysis)
In this paper, we improve the previous results from fixed point theory related to four types of contractions: interpolative Kannan contraction, extended interpolative and Geraghty type contraction, interpolative Hardy-Rogers contraction and Wardowski F-contraction. The basis for our generalization is the results from ``Extended Interpolative Hardy-Rogers-Geraghty-Wardowski Contractions and an Application'' as well as ``On extended interpolative Ćirić-Reich-Rus type F-contractions and an application''.